THE METAPHORICAL AND METONYMIC UNDERSTANDING OF THE TRINITARIAN DOGMA - Barcelona, Antonio (International Journal of English Studies, 2009)
Written in the spirit of cognitive semantics, the paper is an attempt at analysing the limited understanding by Christian believers of the Trinitarian dogma as presented in biblical and theological texts. Though ultimately an insoluble mystery for human reason, the dogma can be shown to have ameasure of metaphorical and metonymic coherence. At the same time, the paper claims that human access to transcendental notions is, in a deep sense, inevitably metaphorical, and consists of an elaborate network of mappings of human-sized notions onto the domain of the divine. This network is claimed to be amanifestation ofthe root metaphor GOD-HUMAN. The author further claims that the opposite root metaphor, HUMAN-GOD, constitutes one of the warrants, together with divine inspiration and the context provided by Revelation, of the truth of statements about God made on the basis of the first root metaphor.